Structural adjustment and intersectoral shifts in Tanzania: a computable general equilibrium analysis - Wobst, Peter (International Food Policy Research Institute, 2001)
Since 1986, Tanzania, like many other countries, has experienced a remarkable political and economic transition. Formerly a one-party state with a planned economy, the country is now multiparty democracy with a market-oriented economy and has undergone a series of economic reforms, including currency evaluation, tariff reduction, domestic tax reforms, and increased investments in infrastructure. The country’s economic performance has improved substantially in many respects. Until now, however, little was known about the effects of the reforms on specific sectors of the Tanzanian economy and on efforts to alleviate poverty in the country. Structural Adjustment and Intersectoral Shifts in Tanzania analyzes how stabilization and structural adjustment policies have affected the country’s economic growth, sectoral performance, welfare, and income distribution. It attempts to determine whether economic reforms have actually made ordinary Tanzanians better off — and if so, which of the country ’s citizens and economic sectors have benefited the most and the least. It focuses in particular on how economic reforms affect the agricultural sector, comparing the effects on agricultural exporters with those on farmers who produce for the domestic market. Through a sophisticated economic model, the study provides much deeper understanding of the workings of the Tanzanian economy than previously available.